Function of Akkermansia muciniphila in type 2 diabetes and related diseases - Li, Jinjie; Yang, Ge; Zhang, Qihe; Liu, Zhuo; Jiang, Xin; Xin, Ying (Frontiers in Microbiology, 2023)
The prevalence of type 2 diabetes (T2D) is increasing worldwide, with many patients developing long-term complications that affect their cardiovascular, urinary, alimentary, and other systems. A growing body of literature has reported the crucial role of gut microbiota in metabolic diseases, one of which, Akkermansia muciniphila, is considered the “next-generation probiotic” for alleviating metabolic disorders and the inflammatory response. Although extensive research has been conducted on A. muciniphila, none has summarized its regulation in T2D. Hence, this review provides an overview of the effects and multifaceted mechanisms of A. muciniphila on T2D and related diseases, including improving metabolism, alleviating inflammation, enhancing intestinal barrier function, and maintaining microbiota homeostasis. Furthermore, this review summarizes dietary strategies for increasing intestinal A. muciniphila abundance and effective gastrointestinal delivery.